King of the wildcatters : the life and times of Tom Slick, 1883-1930 - Miles, Ray. (College Station : Texas A & M University Press, 1996)
"A legend among oilmen, Tom Slick was an independent operator in the truest sense. His office was his buggy during his early days of wildcatting the Mid-Continent oil field around 1910. And even after great success brought him to posher surroundings in an Oklahoma City office suite, his style remained hands-on. His impromptu deals were often brokered on street corners and over the telephone in his typical laconic style. Well into the 1920s he was the last of a breed who had no stock holders or board members to answer to, and instead "worked out of his hip pocket.""--BOOK JACKET. "Slick's extraordinary rise paralleled that of the modern petroleum industry. He began his career in the oil fields of western Pennsylvania, the birthplace of the American oil business. Before 1910, he headed west, traveling with his father and brother to the fields of Kansas to work as contract drillers. Slick met with failure in these early years, as he moved on to Oklahoma in an attempt to locate oil. In 1912 he received the financial backing to drill one more well, which turned out to be the discovery well for the vast Cushing Field. This amazing success was followed by more discoveries of fields - a frenzy of acquiring, drilling, then selling that in 1929 culminated with Slick's sale of his Oklahoma holdings in the Prairie Oil and Gas Company - up until that time, the largest sale of oil properties by an individual."--BOOK JACKET. "In this first biography of Tom Slick, Ray Miles fleshes out the man who, despite his legendary drive - and the high-profile nature of the oil business - was exceedingly private and withdrawn. Miles relies on newspaper accounts, court and business records, correspondence, and personal interviews with family, friends, and associates to render a portrait of one of the most successful and colorful, yet elusive, businessmen of his day."--BOOK JACKET.
"I'm a born trader" -- "Every time I drill a well I have to get another partner" -- "Well, I'll be d----d!" : Tom Slick in the Cushing Field -- In-law entrepreneurs -- "To see the oil gush once more" -- "Seminole is the greatest pool of oil ever discovered" -- "Within a year, I'll be back on top" -- "My whole life has been work, work, work."
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Slick, Tom, -- 1883-1930.; Slick, Tom, -- 1883-1930; Petroleum industry and trade -- United States -- History; Petroleum engineers -- United States -- Biography; Petroleum conservation -- United States -- History; Ingénieurs du pétrole -- États-Unis -- Biographies; Pétrole -- Conservation -- États-Unis -- Histoire; TECHNOLOGY & ENGINEERING -- Petroleum; BIOGRAPHY & AUTOBIOGRAPHY -- Science & Technology; Petroleum conservation; Petroleum engineers; Petroleum industry and trade; United States; Petroleum conservation -- United States -- History; Petroleum engineers -- United States -- Biography; Petroleum industry and trade -- United States -- History; Slick, Tom -- 1883-1930; Biographies; History; Biographies; Biographies